What is Mexico? Portraying the War on Drugs in Documentary Film - Tromp, Rosanne Elisabeth (European Review of Latin American and Caribbean Studies, 2018)
– Cartel Land, directed by Matthew Heineman. United States, 2015.– Kingdom of Shadows, directed by Bernardo Ruiz. Mexico, 2015.– Devil’s Freedom, directed by Everardo González. Mexico/United States, 2017.